INDUKSI PARTENOKARPI BUAH TOMAT (Solanum lycopersicum L.) DENGAN GA3 - ADNYESUARI, A. Agung ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Parthenocarpy tomato (seedless) as the main ingredient needed in the tomato processing industry. This experiment aimed to determine the effect of concentration and frequency of GA3 application to parthenokarpy and fruit characteristics in tomato. The experiment had been conducted at Balai Pengembangan dan Promosi Agribisnis Perbenihan Hortikultura (BPPAPH) Ngipiksari, Laboratory of Genetics and Plant Breeding and Horticulture Laboratory in May-September 2013. Experiment was arranged in factorial Randomized Complete Block Design (RCBD). The first factor consisted of line A134 (V1), 'Kaliurang 206' (V2) and 'Intan' (V3), while the second consisted 0 ppm/without application (K0), 20 ppm one time application (K1), 30 ppm one time application (K2), 20 ppm of three times application (K3) and 30 ppm three times application (K4) of GA3. GA3 was sprayed on the flowers one day before the first flowers bloom on each bunch and every three days after application for three time application. Data were analyzed by analysis of variance, followed by orthogonal contrast test to determine the effect of GA3 concentration on cultivars with 95% confidence level. Data analysis used SAS 9.1 software for Windows. The results showed there was no interaction between the concentration of GA3 with tomato cultivars on all of variables except the number of seeds per fruit. GA3 application three times the concentration of 20 ppm was effective to reduce the number of seeds per fruit in A134 line. Significant effect of GA3 concentration on the number of fruit per cluster and the number of seeds per fruit showed a decrease, while the number of cavities fruit showed an increase. The effect cultivars significant on the number of flowers per cluster variables, number of fruit per cluster, the weight per fruit, fruit weight per bunch, fruit diameter, fruit length, fruit hardness, the amount of cavities fruit, thick flesh, the number of seeds per fruit and fruit TSS (Total Soluble Solid)